Pagelaran Budaya di Sakura Matsuri Sebagai Strategi Diplomasi Untuk Mengundang Masyarakat Indonesia Mengunjungi Jepang - Sri Hastuty, Herawati; Ong, Susy (KIRYOKU, 2025)
The Japanese government actively promotes art and culture through the Japan Foundation to attract the attention of the Indonesian people, thereby fostering emotional closeness and strengthening the relationship between the two countries. As a result, Indonesians will come to like Japanese products and consume Japanese products made in Indonesia as well as those imported from Japan. This will also encourage Indonesian tourists to visit Japan and Indonesian youth to study or work in Japan. This study aims to identify the objectives and benefits of the Sakura Matsuri held in Cikarang and why it was held in that city. This study uses theories of cultural sociology, communication sociology, migration, and soft power. This study uses qualitative methods through internet searches, literature data, and interviews with the committee and visitors. The Sakura Matsuri event held in Cikarang District, Bekasi Regency, West Java Province, is one way Indonesia and Japan are fostering economic cooperation through cultural diplomacy. This event will attract young Indonesians who are new to Japanese culture. Young people who are already familiar with Japan but have not had the opportunity to visit can obtain information at several booths about how to travel to Japan or live in Japan to study or work.